ΑΡΙΣΤΟΤΕΛΙΚΗ ΠΑΙΔΕΙΑ ΚΑΙ ΠΟΛΙΤΙΚΗ ΣΤΗ ΜΕΣΑΙΩΝΙΚΗ ΔΥΣΗ (13ος-14ος ΑΙΩΝΑΣ). Ο DEFENSOR PACIS ΤΟΥ ΜΑΡΣΙΛΙΟΥ ΑΠΟ ΤΗΝ ΠΑΔΟΥΑ - ΓΙΑΝΝΑΚΟΠΟΥΛΟΣ ΔΗΜΗΤΡΙΟΣ Κ. (Eoa kai Esperia, 2013)
Marsiglio Mainardino di Padova (c.1270-1343) was a prominent thinker who made an in-depth analysis of the political works of Aristotle in order to adapt the Greek philosopher’s ideas to a medieval political context, specifically the urban milieu of the Italian city-republics. The paper attempts to underline his crucial political role within the French and German monarchies in the fourteenth century, a role which differentiates Marsiglio from other theoretical scholastics of his time. A clear indication for this was his dynamic participation in the conflict between Pope John XXII and the German Emperor Ludwig IV (1323-1327). Marsiglio’s involvement in this crisis was the culmination of his study of the political situation since the end of the thirteenth century, a study which makes him a unique intellectual. This is the framework within which his main work Defensor Pacis is set. By analyzing the main ideas of this work, the paper aims at highlighting the interaction of Aristotelian ideas with contemporary political and social status, as well as presenting the use of those ideas as “tools” in the hands of daring reformers, such as Marsiglio, towards an innovating transformation of the European establishment.